Responses of Areas 3b and 1 in Anesthetized Squirrel Monkeys to Single- and Dual-Site Stimulation of the Digits - Friedman, Robert M. (American Physiological Society, 2008)
Stimulation of the skin evokes topographically organized activation in somatosensory cortex. This representation is context dependent, however, since a different cortical topography is observed in area 3b when stimulated with complex tactile stimuli that evoke the von Békésy funneling illusion. Here we report on the population responses, as observed with intrinsic optical imaging, of area 1 and area 3b in the anesthetized squirrel monkey to pressure indentation of distal finger pads. Individual finger pad stimulation revealed that area 1 exhibited a smaller magnification factor than 3b, as evidenced by a smaller area of activation elicited by distal finger pad stimulation. Effects of paired finger pad stimulation produced largely similar effects in area 1 and area 3b. Paired finger pad stimulation produced reductions in the area of digit activation in area 1, suggesting the presence of lateral inhibition and funneling of information in area 1. Suppressive effects were stronger for paired stimulations at adjacent than at nonadjacent sites. Single-unit recordings revealed a mixture of either a summation or a suppression of the response to paired finger stimulation, compared with single finger pad stimulation of the primary digit. However, the average population response showed that paired finger pad stimulation resulted in response suppression. Based on this study and previous studies, we suggest the presence of at least three distinct ranges of lateral inhibition in areas 3b and 1.